Burnout and job satisfaction of primary school teachers in southern Papua - Agustinus Kia Wolomasi; Basilius Redan Werang (Faculty of Education, Universitas Negeri Yogyakarta, 2022)
This study intended to investigate the potential correlation between burnout and job satisfaction of teachers in the elementary schools of Southern Papua, Indonesia. To attain the objective of the study, two survey questionnaires were distributed to 1277 teachers who were conveniently established as samples. Utilizing the SPSS version 21, obtained data were statistically analyzed using the van Pearson’s correlation analysis technique. Result of the Pearson’s correlation statistical analysis showed a significant negative correlation between the teachers’ burnout and their job satisfaction. The outcome of study provides guidance for the government education policymakers in the area of Southern Papua to eliminate teachers’ burnout in order to promote the elementary school teachers’ job satisfaction.